Lady Macbeth, her book - Sonnenschein, Dana (Embark: A Literary Journal for Novelists, 2022)
A.D. 1034 The king and queen took hawks out that day, and their retinue trailed along hills and swales, watching as Duncan and then Suthen lifted gauntleted arms and opened their fists. The hunting…
Keywords: dept.eng; ⛔ No DOI found